2019
DOI: 10.1007/s00726-019-02776-5
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids do not improve muscle recovery from resistance exercise in untrained young adults

Abstract: The purpose of this study was to investigate the effects of BCAA supplementation on muscle recovery from resistance exercise (RE) in untrained young adults. Twenty-four young adults (24.0 ± 4.3 years old) were assigned to 1 of 2 groups (n = 12 per group): a placebo-supplement group or an BCAA-supplement group. The groups were supplemented for a period of 5 days. On day 1 and 3, both groups underwent a RE session involving two lower body exercises (hack squat and leg press) and then were evaluated for muscle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, arginine administration resulted in increased protein synthesis [36]. Meanwhile, BCAA supplementation did not improve muscle recovery from intense resistance exercise in young adults [41]. Thus, BCAAs and arginine appear to be able to prevent and/or improve age-related muscle atrophy, i.e., sarcopenia.…”
Section: Amino Acids In the Regulation Of Muscle Massmentioning
confidence: 99%
“…Additionally, arginine administration resulted in increased protein synthesis [36]. Meanwhile, BCAA supplementation did not improve muscle recovery from intense resistance exercise in young adults [41]. Thus, BCAAs and arginine appear to be able to prevent and/or improve age-related muscle atrophy, i.e., sarcopenia.…”
Section: Amino Acids In the Regulation Of Muscle Massmentioning
confidence: 99%
“…This apparent disconnect between mTOR signaling and protein synthesis seems to be explained by a temporal discrepancy between both processes [150]. Still, BCAA supplementation did not improve muscle soreness and function during recovery of untrained young adult (average age of 24 years old) from resistance exercise [151]. Overall, more than BCAA supplements, the ingestion of high-quality protein boosts protein synthesis following exercise training, improving muscle health.…”
Section: Amino Acids Pool and Protein Turnovermentioning
confidence: 99%
“…These amino acids are involved in muscle protein resynthesis [21]. Data suggest that leucine plays a major role in regulating the intracellular signaling pathways for protein synthesis [20].…”
Section: Branch Chain Amino Acidsmentioning
confidence: 99%
“…These authors have reported data supporting that BCAA are the only amino acids metabolized directly in the muscles, inferring that protein resynthesis is highly plausible. Still, the use of BCAA in alleviating muscle soreness and repair among athletes remains warranting [21]. However, the consumption and function of BCAA should be accompanied by other essential amino acids (EAA) to support these processes of muscle resynthesis [20].…”
Section: Branch Chain Amino Acidsmentioning
confidence: 99%